ANALISIS PERAN UMKM DALAM MEMBANGUN PEREKONOMIAN KELUARGA DI MASA PANDEMI.COVID. (Studi Kasus Pada Jasa Griya Rias ‘Pengantin Ayu Ningsih Wedding’) - TEGUH SANTOSA; TRISNAWATI KUSUMAWARDHANI (Develop: Jurnal Ekonomi Pembangunan, 2020)
Pandemics have an impact on the economy of a country. This is also felt by all levels of society. The family economy began to experience imbalances, due to a ban on activities outside the home at the beginning of the pandemic that hit Indonesia. The use of bridal makeup services has decreased significantly due to a temporary ban from the government to eliminate large crowds. This happened during March 2020. In early June 2020, the government implemented a new normal, where people are allowed to carry out activities outside the home but must continue to implement and comply with the Pandemic Health Protocol, Covid. Post June 1, 2020, the Indonesian economy is gradually moving towards the recovery stage. The national economy slowly returned to normal. Related to this, the active automatic movement of UMKM has begun to run again. And one of the UMKM that was affected by the pandemic.covid is the service of Rias Griya AyuNingsih-a wedding which is located at Jalan Raya Kemangsari, Jatibening Baru, Pondok Gede, Bekasi.